Enhanced mechanical properties of wood ash and fly ash as supplementary cementitious materials. (3rd October 2017) - Hussain, Zaib; Maqsood, Rohama; Din, Muhammad Imran; Khan, Shahzad Maqsood; Shahnaz, Akhtar; Rashid, Mohsin; Ameen, Saba
ABSTRACT: The incorporation of fly ash (FA) and wood ash (WA) in concrete as supplementary cementitious materials (SCM) was studied. The chemical composition of ordinary Portland cement, FA and WA was determined according to ASTM C-114. SEM and optical microscopy were used for the analysis of concrete. Setting time, compressive strength, water absorption and acid resistance of the concrete with different percentages of SCM ranging from 0 to 60% were evaluated. The results obtained showed that setting time and rate of water absorption increased with the increase in percentage of SCM. After 7 and 28 days, the compressive strength of concrete with 20% FA as SCM was higher than that with substitution with 20% WA. Resistance of concrete against sulphate attack increased with an increase in the percentage of FA. It was found that incorporating more than 20% WA resulted in a decrease in sulphate attack resistance.